Effect of Alpha Lipoic Acid on Polycystic Ovary Syndrome with Insulin Resistance (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in reproductiveage women where insulin resistance plays an important role. Insulin resistance makes the first line treatment,clomiphene citrate (CC) treatment, become ineffective. Alpha Lipoic Acid (ALA) is believed to be analternative treatment for CC-resistant PCOS. Objectives: The aim of the study is to understand the effectof ALA in Insuline receptor substrate 1 (IRS-1) expression, Glucosa transporter 4 (GLUT-4) expression,and folliculogenesis in insulin resistant PCOS rat model. Methods: This was an experimental study withrandomized posttest only control group design. 30 females rat injected with testosterone propionate (TP)1mg/100gram bodyweight for 28 days then divided into 3 groups. Negative control group receive no othertreatment, positive control group receive a placebo for 14 days, and treatment group receive ALA for 14 days.IRS-1 and GLUT-4 expression is evaluated with immunohistochemistry, while folliculogenesis is evaluatedby counting the number of follicle in each stage. Results: Mean IRS-1 expression in muscle in treatmentgroup is significantly higher than other groups (4.28±1.05; 3.02±1.03; 1.86±0.83, p <0.01 respectively).Mean GLUT-4 expression in treatment group is significantly higher than other groups (4.28±0.91; 3.20±1.14;1.40±0.55, p <0.01 respectively). Mean number of follicle in each stage in treatment group are significantlyreduced than other groups (all p <0.05). Conclusion: ALA increase the expression of IRS-1 and GLUT-4,and also reduce the number of follicle in each stage of folliculogenesis.